(untitled) (Web of Teachers: Inderscience Research, 2025)
This scientific article is devoted to the study of performing schools of playing the dutor, a unique musical instrument common in Central Asia. The focus is on the work of the outstanding Uzbek musician Turgun Alimatov, whose performing style had a significant influence on the development of dutor art. The relevance of the study is due to the need to preserve and develop the traditions of playing the dutor, as well as the importance of studying the contribution of Turgun Alimatov to the formation of a separate performing school. His work is a shining example of high professionalism and skill, and his performing style deserves special attention and study. The purpose of the study is to identify the features of the performing style of Turgun Alimatov and its influence on the formation of a separate performing school of playing the dutor.